Liver condemnation due to bovine and buffalo fasciolosis in Antioquia province, Colombia - Quiroga-Robayo, Mayra A; Uruburu, Mónica; Loaiza-Echeverri, Erica T; Badel Mogollon, Jaime; Correa Valencia, Nathalia M; Carrillo Bonilla, Lina (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Fasciola hepatica affects cattle and buffaloes causing decreased production and liver condemnation at slaughter. Objective: To determine liver condemnation frequency, temporal distribution, and associated factors, as well as the spatial distribution and economic impact of F.hepatica infection based on postmortem inspection of cattle and buffaloes processed between 2010 and 2019 at one of the main slaughterhouses in Colombia. Methods: An observational, descriptive, and cross-sectional study was carried out, with a convenience non-probability sampling. Temporal distribution of liver condemnation frequency was analyzed. Pearson χ2 test was used to determine association between the dependent variable (i.e., presence/absence of adult parasites of F.hepatica) and frequency rates between months and years. Monthly rainfall data was compared with the accumulated monthly frequency. Association between the dependent variable and production type (i.e., industrial-type bovine cattle —intended for milk production, and commercial-type bovine cattle —intended for meat production), weight, and sex (odds ratios, OR and confidence intervals, 95% CI) was explored. Descriptive maps of the municipalities presenting at least one positive case of F.hepatica in 2019 and weighted prevalences, both for bovines and buffaloes, were designed. Only losses due to liver condemnation between 2010 and 2019 were considered in the economic impact analysis. Results: A total of 1,947,233 animals were processed during the study period, resulting in 3.1% overall frequency of fasciolosis. Industrial-type cattle presented 7.4% higher risk of developing F.hepatica compared to commercial-type cattle (OR=0.074; 95% CI:0.07–0.08). Likewise, male cattle presented 3.88 times more risk compared to females (OR=3.88; 95% CI:3.49–4.33). Economic losses due to liver condemnation were estimated at US$1,129,660 for the study period. Conclusion: This is the first report of Fasciola hepatica in buffaloes in Colombia. Liver condemnations in Colombia occur throughout the year, although its frequency increases during the rainy season. The economic losses, estimated by liver condemnation due to fasciolosis, are high; however, it is necessary to explore such losses considering other productive indicators and larger animal populations. This work demonstrates the importance of systematizing the information generated in slaughterhouses.